(1+sin4θ-cos4θ)/(1+sin4θ+cos4θ)=(2sin2θcos2θ+2sin²2θ)/(2sin2θcos2θ+2cos²2θ)=sin2θ/cos2θ=tan2θ=2tanθ/(1-tan²θ)∴(1+sin4θ-cos4θ)/2tanθ=(1+sin4θ+cos4θ)/(1-tan²θ)
求证1+sin4θ-cos4θ 1+sin4θ+cos4θ——————= ———————— 2tanθ 1-tan
2个回答
相关问题
-
求证:[1+sin4θ−cos4θ/2tanθ]=[1+sin4θ+cos4θ1−tan2θ
-
求证:2(cos θ -sin θ )/(1+sinθ +cosθ)=tan(∏/4- θ /2)-tan(θ /2)
-
证明恒等式,1+sin4θ-cos4θ/2tanθ=1+sin4θ+cos4θ/1-tan²θ..
-
求证:(1-tanθ)/(1+tanθ)=(1-2sinθcosθ)/(cos2θ-sin2θ)
-
求证sinθ(1+tanθ)+cosθ(1+1/tanθ)=1/sinθ+1/cosθ
-
求证:tanθ*sinθ/tanθ-sinθ=1+cosθ/sinθ
-
若兀/4tanθB.cosθ>tanθ>sinθC.sinθ>tanθ>cosθD.tanθ>sinθ>cosθ
-
求证 (sinθ+cosθ-1)(sinθ-cosθ+1)) /sin2θ=tanθ/2
-
sin^2(θ)+4cosθ/sin(90-θ) -1/tan(90-θ)
-
cosθ/(1+cosθ)=-4,且(1/2)^sinθ>1,求tan(θ/2)